2012
DOI: 10.1111/j.1744-6155.2012.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status among pediatric cancer patients: A comparison between hematological malignancies and solid tumors

Abstract: Adequate dietary intake is important for pediatric cancer patients, but nurses need to pay more attention to the diets of patients with solid tumors as compared with those with hematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Considering that approximately 50% of the patients had Stage III or IV disease and that the cutoff for malnourishment was designated as higher than traditional values of BMI (<18.5) and TSF/MAMC (<5%), DLBCL patients may be less likely to have nutritional deficiency than patients with solid cancers. This is consistent with the results of a previous study that demonstrated a more frequent occurrence of malnutrition in solid cancers than hematologic malignancies (19).…”
Section: Discussionsupporting
confidence: 93%
“…Considering that approximately 50% of the patients had Stage III or IV disease and that the cutoff for malnourishment was designated as higher than traditional values of BMI (<18.5) and TSF/MAMC (<5%), DLBCL patients may be less likely to have nutritional deficiency than patients with solid cancers. This is consistent with the results of a previous study that demonstrated a more frequent occurrence of malnutrition in solid cancers than hematologic malignancies (19).…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained by Tah et al . [ 21 ] suggested that the loss of appetite (89.2%), vomiting (81.1%), and nausea (54.1%) were the most frequent problems of children diagnosed with a solid tumor. In addition, Hedén et al .…”
Section: Discussionmentioning
confidence: 99%
“…When treating these patients, the challenge faced by the dietitian is to prevent further deterioration of nutritional status and to attempt to reverse any deterioration in nutritional status that may have already occurred. Children with solid tumours in particular are often in need of nutritional interventions as they practice food restrictions more often and may experience significantly worse eating problems including nausea, vomiting and loss of appetite …”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has emphasised the importance of including arm anthropometry measurements, specifically mid‐upper arm circumference (MUAC) and triceps skinfold thickness (TSFT), as part of the classification criteria as these measurements are independent of tumour size . Utilisation of biochemistry (namely albumin) and anthropometry measurements in combination has been shown to improve the sensitivity of classification of nutritional status …”
Section: Introductionmentioning
confidence: 99%